Diastereoselective Synthesis of Dispiropseudoindoxyls and Preparation of 9-Oxopyrrolo[ 1,2-α]Indoles - S. Velezheva, Valeriya; N. Fedorova, Irina; L. Babii, Olesya; A. Anisimov, Alexei; S. Bushmarinov, Ivan; S. Peregudov, Aleksander (Current Organic Synthesis, 2015)
Reported here are two novel cationic domino reactions of 2-arylmethylideneindoxyls leading to the formation of highly substituted dispiropseudoindoxyls or 9-oxo-pyrrolo[1,2-α]indoles. The outcome of the reactions can be controlled by the appropriate choice of an acid or the application of an external nucleophile. The dispirocyclodimers are formed in single diastereomeric forms with three stereogenic centers, with two of those being quaternary. The reactions provide approaches to the spiropseudoindoxyl and pyrrolo[1,2-α]indole ring systems, common components in natural spiropseudoindoxyl alkaloids and pyrrolo[1,2-α]indole biologically active molecules.
Keywords: 2-Arylmethylideneindoxyls